Peter Marshall and Catherine Marshall papers - Marshall, Peter, 1902-1949.; Marshall, Catherine, 1914-1983.; Marshall, Catherine, 1914-1983.; Marshall, Catherine, 1914-1983.; Marshall, Catherine, 1914-1983.; Marshall, Catherine, 1914-1983.; Marshall, Catherine, 1914-1983.; Marshall, Peter, 1902-1949.; Marshall, Peter, 1902-1949.
Correspondence, writings, notes, and sermons of Peter Marshall along with correspondence, writings, movie scripts, scrapbooks, and other papers of Catherine Marshall. Material pertaining to the production of the movie, A Man Called Peter, based on Catherine Marshall's book published in 1951 and produced by Twentieth Century-Fox Film Corporation in 1955 includes film scripts, production material such as records of conferences attended by Marshall and studio representatives, and correspondence with actors Jean Peters, Marjorie Rambeau, and Richard Todd; screenwriter Eleanore Griffin; and producer Samuel G. Engel. Writings include drafts and related material for Peter Marshall's book titled Mr. Jones, Meet the Master, Sermons and Prayers (1949); Catherine Marshall's books, A Man Called Peter, the Story of Peter Marshall (1951), Friends with God, Stories and Prayers of the Marshall Family (1956), To Live Again (1957), and Beyond Our Selves (1961); and their collaborative work, God Loves You, Our Family's Favorite Stories and Prayers (1953).
Microfilm edition of sermons available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Peter Marshall, Presbyterian clergyman and chaplain of the U.S. Senate, and his wife, Catherine Marshall, author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Engel, Samuel G., -- 1904-1984 -- Correspondence; Griffin, Eleanore -- Correspondence; Marshall, Peter, -- 1902-1949.; Peters, Jean, -- 1926-2000 -- Correspondence; Rambeau, Marjorie, -- 1889-1970 -- Correspondence; Todd, Richard, -- 1919-2009 -- Correspondence; Marshall family; Twentieth Century-Fox Film Corporation; Man Called Peter (Motion picture); American literature; Bereavement -- Religious aspects -- Christianity; Children -- Religious life; Christian life; Clergy -- United States; Faith; Families -- Religious life; Motion pictures; Presbyterian Church -- Clergy; Presbyterian Church -- Sermons; Religion; Sermons, American -- 20th century; Spouses of clergy -- United States; Chaplains, U.S. Senate; Clergy